1997
DOI: 10.1063/1.473432
|View full text |Cite
|
Sign up to set email alerts
|

Volume-phase transition of N-isopropylacrylamide gels induced by hydrostatic pressure

Abstract: Pressure-induced volume phase transitions in neutral and ionized N-isopropylacrylamide-water (NIPA) gels were investigated. When the pressure is increased, the gels which shrink at atmospheric pressure undergo two volume phase transitions. One is the continuous phase transition (for neutral gels) or the discontinuous phase transition (for ionized gels) from the shrunken state to the swollen state at low pressures of several tens MPa. Another is the gradual shrinking transition occurred in the high pressure reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 20 publications
4
50
0
Order By: Relevance
“…This indicates that states of hydrophobic solvation are different in the low-pressure (PoP 0 ) and highpressure (P4P 0 ) regions. Such a reentrant phase diagram was observed not only in water soluble polymers [58][59][60] but also in biomacromolecules. 61 We have discussed the reason for the convexity of the phase diagram in previous work.…”
Section: Phase Behaviors Of Polymer Gels and Block Copolymer Aqueous mentioning
confidence: 92%
“…This indicates that states of hydrophobic solvation are different in the low-pressure (PoP 0 ) and highpressure (P4P 0 ) regions. Such a reentrant phase diagram was observed not only in water soluble polymers [58][59][60] but also in biomacromolecules. 61 We have discussed the reason for the convexity of the phase diagram in previous work.…”
Section: Phase Behaviors Of Polymer Gels and Block Copolymer Aqueous mentioning
confidence: 92%
“…Recently, the author reported that hydrogels, such as PNIPA gels in water 11 and poly(acrylamide) gels in acetone-water mixtures, 12 underwent volume phase transitions by a change in hydrostatic pressure, the pressure-induced volume phase transition. The pressure-induced volume phase transition can be explained by taking account of the free energy difference derived from the volume change accompanying the hydration of the network polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, an alternative to temperature is provided by hydrostatic pressure, which is also known to change the polymer-solvent mixing of pNIPAM gels. [39][40][41][42][43] The influence of pressure over the swelling of microgel particles, however, has never been explored, despite the fact that pressure changes can be achieved in very short times, as they propagate at the speed of sound of the material, and occur homogeneously throughout the sample. The major drawback is, however, the need of a pressure chamber, which often requires substantial technical efforts.…”
Section: Introductionmentioning
confidence: 99%